Finite volume method for a diffusion-advection equation - Goh, Brandon B Edison Adi (Nanyang Technological University, 2024)
Computational fluid dynamics (CFD) is an emerging tool to simulate fluid motions and will continue to be increasingly more prominent with greater computational power. Coupled with the principles of the finite volume method to solve the diffusion-advection equation, a well-defined computer program can provide numerical solutions to a governing equation following the variables and constraints in a mathematical problem.